The Effect of Classic Music Therapy and Lavender Aromatherapy Candles on Anxiety Levels of Trimester III Pregnant Women - Siti Romlah; Joko Sapto Pramono; Heni Suryani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
High levels of anxiety or depression during pregnancy can pose risks such as stunted fetal growth and premature birth. Music is believed to be used for relaxation, stress relief and anxiety reduction because music is an organized auditory stimulus consisting of melody, rhythm, harmony, shape and style. Aromatherapy is also a non-pharmacological treatment that uses essential oils and stimulates the olfactory system to reduce stress and create a sense of calm. The aim of this study was to determine the effect of classical music therapy and aromatherapy candles on the anxiety level of third trimester pregnant women. This research method is a pre-experimental quantitative type. The design used in this study was one group pretest posttest, the population in this study were third trimester pregnant women in the Karangan Health Center area. The sampling technique was simple random sampling of 44 third trimester pregnant women. Data were analyzed using the Wilcoxon test. The results showed that the level of anxiety before the intervention experienced by most of the respondents was moderate anxiety in the number of 21 respondents (47.7%) and the level of anxiety after the intervention was mostly with mild anxiety in the number of 20 respondents (45.5%). The results of the bivariate analysis showed that there was an effect of classical music therapy and lavender aromatherapy candles on reducing the anxiety level of third-trimester pregnant women with a result (p=0.000) smaller than (<0.05). The anxiety level score in the pre-test measurement is higher than the post-test measurement, indicated by the mean value in the pretest (23.57) higher than the posttest (19.16) which means there is a decrease in the anxiety level score in the respondents before and after intervention.